The Effectiveness Of The Combination Of Acupressure Therapy With Oxytocin Massage Against The Length Of Time Of Milk Production In Puerperal Mothers - Indah Susilowati; Feva Tridiyawati (International Journal of Health and Pharmaceutical (IJHP), 2023)
According to the UNICEF report, there were 54 neonatal infant deaths per 1,000 live births worldwide in 2020. The highest neonatal mortality rate in 2020 was found in the Sub-Saharan Africa region, namely 27 deaths per 1,000 live births. In Indonesia, only 1 out of 2 babies under 6 months is exclusively breastfed, and only a little more than 5% of children are still getting breast milk at 23 months of age. Nationally, the coverage of babies receiving exclusive breastfeeding in 2019 is 67.74%. The inhibiting factor in breastfeeding is the production of breast milk which is less and slow to come out which can cause the mother not to give her baby enough. A method that is rarely used to speed up milk release and stimulate milk productivity is a combination of acupressure therapy and oxytocin massage. Knowing the effectiveness of the combination of acupressure therapy with oxytocin massage on the length of time to express breast milk in postpartum mothers. Quasi experimental with posttest only control group design. The sample in this study were all postpartum mothers at BPM. Indah Susilowati in August-October 2022 as many as 30 people, the sampling technique is total sampling. The average time for breastfeeding in the intervention group was 2.16 hours and in the control group 2.79 hours. There is the effectiveness of the combination of acupressure therapy with oxytocin massage on the length of time for expressing milk in postpartum women with a p value of 0.000. There is an effective combination of acupressure therapy with oxytocin massage on the length of time to express breast milk in postpartum mothers. The combination of acupressure therapy and oxytocin massage can be considered as an alternative effort to accelerate breastfeeding in postpartum mothers.